(untitled) (Economics and region, 2025)
The article examines inclusive development as a key strategic guideline for the modernization of Ukraine’s national economy amid socio-economic transformation and external instability. Inclusive development is viewed not only as a socially oriented model of economic growth but as a comprehensive concept that combines the principles of sustainable development, social justice, effective institutional governance, and equal access to economic opportunities. The study analyzes scientific approaches to interpreting inclusivity, presents the results of a comparative analysis of domestic and international experience, and identifies the main factors hindering the achievement of an inclusive development model in Ukraine. The essence and role of institutional, financial, and social mechanisms in ensuring inclusive modernization are revealed, and the necessity of transitioning to a new type of economic policy focused on achieving a balance between economic efficiency and social responsibility is substantiated. The directions of state intervention are systematized to expand economic participation of the population, reduce inequality, ensure regional balance, and increase access to high-quality public goods. The paper also proposes a system of indicators for monitoring the effectiveness of inclusive reforms, which allows for an objective assessment of the effectiveness of inclusive development policy at the national level. It is concluded that it is appropriate to integrate inclusive principles into Ukraine’s strategic economic planning documents, which will create the foundation for fair, sustainable, and comprehensive economic growth. In light of the challenges posed by war, demographic shifts, and rising inequality, the study emphasizes the urgency of embedding inclusivity into the national development agenda. Only by prioritizing human-centered policies and addressing structural barriers can Ukraine achieve a resilient and future-oriented economic trajectory.